Database Comparison of the Adult-to-Adult Living Donor Liver Transplantation Cohort Study (A2ALL) and the SRTR U.S. Transplant Registry,, - Gillespie, BW (2010)
Data submitted by transplant programs to the Organ Procurement and Transplantation Network (OPTN) are used by the Scientific Registry of Transplant Recipients (SRTR) for policy development, performance evaluation, and research. This study compared OPTN/SRTR data with data extracted from medical records by research coordinators from the nine-center A2ALL study. A2ALL data were collected independently of OPTN data submission (48 data elements among 785 liver transplant candidates/recipients; 12 data elements among 386 donors). At least 90% agreement occurred between OPTN/SRTR and A2ALL for 11/29 baseline recipient elements, 4/19 recipient transplant or follow-up elements, and 6/12 donor elements. For the remaining recipient and donor elements, >10% of values were missing in OPTN/SRTR but present in A2ALL, confirming that missing data were largely avoidable. Other than variables required for allocation, the percentage missing varied widely by center. These findings support an expanded focus on data quality control by OPTN/SRTR for a broader variable set than those used for allocation. Center-specific monitoring of missing values could substantially improve the data.